2022
DOI: 10.1186/s12916-022-02612-w
|View full text |Cite
|
Sign up to set email alerts
|

The causal associations of circulating amino acids with blood pressure: a Mendelian randomization study

Abstract: Background Circulating levels of amino acids were associated with blood pressure (BP) in observational studies. However, the causation of such associations has been hypothesized but is difficult to prove in human studies. Here, we aimed to use two-sample Mendelian randomization analyses to evaluate the potential causal associations of circulating levels of amino acids with BP and risk of hypertension. Methods We generated genetic instruments for ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
2
21
2
Order By: Relevance
“…Recent research has suggested that elevated BCAAs levels might be linked to an increased risk of developing hypertension 33,34 . Furthermore, another study showed a direct causal relationship between higher circulating BCAAs levels and elevated blood pressure 35 . Here, we did not observe a causal effect for BCAAs on SBP and hypertension, but we did find a causal relationship between BCAAs and antihypertensive medication use.…”
Section: Discussioncontrasting
confidence: 74%
“…Recent research has suggested that elevated BCAAs levels might be linked to an increased risk of developing hypertension 33,34 . Furthermore, another study showed a direct causal relationship between higher circulating BCAAs levels and elevated blood pressure 35 . Here, we did not observe a causal effect for BCAAs on SBP and hypertension, but we did find a causal relationship between BCAAs and antihypertensive medication use.…”
Section: Discussioncontrasting
confidence: 74%
“…Genetically proxied plasma glycine level appears to be protective against the development of CAD and HT, while branched chain amino acids (i.e. valine, leucine, and isoleucine) are genetically associated with elevated BP levels [93][94][95][96]. Importantly, analyses restricted to genetic variations in genes directly involved in glycine metabolism found no causal effect on the level of BP, which suggests possible pleiotropic effects (i.e.…”
Section: Emerging Proteomic and Metabolomic Tools For Testing Causal ...mentioning
confidence: 94%
“…UK Biobank, whose first release of metabolic data includes nine amino acids (Gly, Gln, His, Tyr, Phe, Ala, Val, Ile, and Leu), is a comprehensive prospective cohort study that contains approximately half a million UK participants (Bycroft et al, 2018; Sudlow et al, 2015). Lin et al (2022) performed GWAS analysis for circulating amino acid concentration in the UKB samples of European races for which the metabolomic data were available ( n = 98 317). The summary‐level data of an external GWAS (Kettunen et al, 2016) including more than 20 000 European participants were meta‐analyzed with Chenhao Lin's GWAS results afterward (Lin et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al (2022) performed GWAS analysis for circulating amino acid concentration in the UKB samples of European races for which the metabolomic data were available ( n = 98 317). The summary‐level data of an external GWAS (Kettunen et al, 2016) including more than 20 000 European participants were meta‐analyzed with Chenhao Lin's GWAS results afterward (Lin et al, 2022). From the results of this meta‐analysis, amino acid‐related SNPs with p values <5.0 × 10 −8 were selected for two‐sample MR analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation